Ayurvedic Management Of Anovulation - A Clinical Case Report. - Patil , Suma; Narayan , Vidya; Busari , Sukanya; Mujawar , Anjum Maheboobpasha (Journal of Neonatal Surgery, 2025)
Background: Primary infertility is defined as the inability of a couple to achieve conception after one year of unprotected coitus. Anovulation is a significant cause of female infertility, contributing to approximately 35% of cases attributed to ovulatory dysfunction. It is characterized by the failure of follicular rupture despite follicular development, resulting in the absence of ovulation. The etiologies of anovulation are diverse and include polycystic ovary syndrome (PCOS), hyperprolactinaemia, premature ovarian insufficiency, hypothalamic anovulation, luteinized unruptured follicle syndrome, and luteal phase deficiency. Acharya Kashyapa in the Revati Kalpa Adhyaya describes a condition termed Pushpagni Jataharini, characterized by the lakshana "Vr̥tta Pushpa" referring to timely but fruitless menstruation. From an Ayurvedic perspective, this clinical presentation can be correlated with anovulation. Case report: A 31-year-old female patient who has been trying to conceive for the past three years presented for Ayurvedic consultation and treatment. Following evaluation, she was diagnosed with primary infertility due to anovulation and elevated prolactin levels. In this particular case, the primary Doshas involved were predominantly Vata and Kapha, along with vitiation of the Dhatus - Rasa, Rakta, and Artava. Therefore, the treatment was formulated based on the prevailing Dosha dominance and the affected Dhatus incorporating both Shodhana i.e., Vamana, Basti, Uttarabasti and Shamana therapies Results: Patient conceived after over one year of Ayurvedic line of treatment with regular follow-up. UPT was found positive on February 2025. Conclusion: This case study concludes that the comprehensive and holistic principles of Ayurveda contribute significantly to the management and alleviation of infertility resulting from ovarian dysfunction